Improving access to chemotherapy through enhanced capacity planning and patient scheduling. Issue 1 (2nd January 2019) - Liu, Emma; Ma, Xiang; Sauré, Antoine; Weber, Leah; Puterman, Martin L.; Tyldesley, Scott
Abstract: As a consequence of a growing demand for chemotherapy, it has become increasingly important for cancer care providers to make informed process configuration, capacity planning and patient scheduling decisions in order to use medical resources efficiently and ensure that patients receive timely access to care. To support this decision-making process at an oncology clinic in British Columbia, Canada, we performed a process analysis and a simulation study to investigate the impact of simultaneous changes in demand level, chemotherapy staffing levels and appointment scheduling practice, evaluated by clinic overtime and patient in-clinic wait times. This study not only provides a methodological framework for improved short-term and long-term chemotherapy planning, but also offers precise implementable recommendations that are now being considered by decision makers.